2001
DOI: 10.1038/sj.cdd.4400808
|View full text |Cite
|
Sign up to set email alerts
|

Pro-caspase-3 overexpression sensitises ovarian cancer cells to proteasome inhibitors

Abstract: The ubiquitin-proteasome pathway plays a critical role in the degradation of several proteins involved in the cell cycle. Dysregulation of this pathway leads to inhibition of cellular proliferation and the induction of apoptosis. Ubiquitination and its downstream consequences have been investigated intensively as targets for the development of drugs for tumour therapy. Here we have investigated the mechanism of apoptosis induced by the proteasome inhibitors MG-132, lactacystin and calpain inhibitor I (ALLN), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…22,23 Previous work from our group has indicated that it is possible to derive ovarian carcinoma cell clones that stably express caspase-3, 25 following transfection with the tricistronic tetracycline -regulatable plasmid, pNRTIS ± caspase-3, and selection by growth in medium containing the neomycin analogue, G418. The level of intrinsic procaspase -3 expression differs in the two cell populations investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Previous work from our group has indicated that it is possible to derive ovarian carcinoma cell clones that stably express caspase-3, 25 following transfection with the tricistronic tetracycline -regulatable plasmid, pNRTIS ± caspase-3, and selection by growth in medium containing the neomycin analogue, G418. The level of intrinsic procaspase -3 expression differs in the two cell populations investigated.…”
Section: Discussionmentioning
confidence: 99%
“…27 Fulllength human caspase -3 cDNA was generated by reverse transcriptase polymerase chain reaction ( PCR ) from OVCAR3 cells and cloned as an EcoRI fragment into pNRTIS -33. 25 Plasmid maps are presented in Figure 1a.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 These data together with our results support the hypothesis that in cancer cells caspases are continuously activated at minimal levels and kept in frame by IAPs. 60,62,63,17 It is clear that further studies are required to confirm this hypothesis. In conclusion, our data indicate that PIs, by sustaining the levels of the IAPs antagonist Smac/DIABLO, can overcome this distal apoptotic checkpoint and they could be powerful drugs to induce cell death of cancer cells that have accumulated mutations in the apoptosome, both as a single agent or in combination with other antitumor treatments.…”
Section: Discussionmentioning
confidence: 95%
“…25,26 Overexpression or restoration of pro-caspase-3 was able to sensitize ovarian and breast cancer cells to treatment. 27,28 Here, we investigated the expression status of two executioner caspases, caspase-3 and caspase-7, in a panel of primary breast carcinomas and tried to analyze whether or not there is a correlation between expression of pro-and active enzymes, apoptotic index, tumor grade and other clinical or morphological parameters.…”
Section: Introductionmentioning
confidence: 99%